From Block Grants to Performance Governance: An Agency Theory Investigation of Public University Funding Reform Readiness in Malaysia - Ahmad, Abd Rahman; Md Sapry, Hairul Rizad; Jameel, Alaa S; M. Hassan, Mohamud (JBS Nexus, 2026)
The Ministry of Higher Education is addressing the systemic efficiency gap in Malaysia's public universities through the New Funding Formula (NFF) as part of the Malaysia Education Blueprint 2015–2025. Although government funding for higher education has increased by 14% annually, the country ranks 45th out of 50 in terms of educational output. This study is the first empirical examination of NFF implementation readiness using Agency Theory in all 20 public universities in Malaysia at the same time. Three senior higher education funding specialists provided qualitative data, and 107 top management officials from Research, Comprehensive, and Focused universities provided quantitative data using an exploratory sequential mixed-methods design. Goals and Objectives, Outcome, Agency Relationship, Risk, Agent Ability, and Monitoring were the six-agency theory-based strategic constructs that were assessed. Agent Ability (rs = 0.605, ? = 0.249, p